Gastroesophageal Reflux Disease (IntechOpen, 2019)
Gastroesophageal reflux disease (GERD) is a very common, global clinical problem. It affects any age group, both males and females, and is seen mainly in developed countries, especially among obese individuals. GERD needs to be treated to prevent nuisance symptoms and long-term complications. The book deals with the diagnosis of GERD, including clinical presentations and diagnostic investigations, and describes the different available conservative, medical, surgical and endoscopic treatments. The book also covers gastroesophageal disease in children, its presentation and treatment. It also deals with the refractory type of gastroesophageal disease including different theories. It is very useful for gastroenterologists and upper gastrointestinal surgeons.